The Oncidium Ethylene Synthesis Gene Oncidium 1-Aminocyclopropane-1 Carboxylic Acid Synthase 12 and Ethylene Receptor Gene Oncidium ETR1 Affect GA–DELLA and Jasmonic Acid Signaling in Regulating Flowering Time, Anther Dehiscence, and Flower Senescence in Arabidopsis - Huang, Tzu-Hsiang; Hsu, Wei-Han; Mao, Wan-Ting; Yang, Chang-Hsien (Frontiers in Plant Science, 2022)
In plants, the key enzyme in ethylene biosynthesis is 1-aminocyclopropane-1 carboxylic acid synthase (ACS), which catalyzes S-adenosyl-L-methionine (SAM) to ACC, the precursor of ethylene. Ethylene binds to its receptors, such as ethylene response 1 (ETR1), to switch on ethylene signal transduction. To understand the function of ACS and ETR1 in orchids, OnACS12 and OnETR1 from Oncidium Gower Ramsey were functionally analyzed in Arabidopsis. 35S::OnACS12 caused late flowering and anther indehiscence phenotypes due to its effect on GA–DELLA signaling pathways. 35S::OnACS12 repressed GA biosynthesis genes (CPS, KS and GA3ox1), which caused the upregulation of DELLA (GAI, RGL1 and RGL2) expression. The increase in DELLAs not only suppressed LFY expression and caused late flowering but also repressed the JA biosynthesis gene DAD1 and caused anther indehiscence by downregulating the endothecium-thickening-related genes MYB26, NST1 and NST2. The ectopic expression of an OnETR1 dominant-negative mutation (OnETR1-C65Y) caused both ethylene and JA insensitivity in Arabidopsis. 35S::OnETR1-C65Y delayed flower/leaf senescence by suppressing downstream genes in ethylene signaling, including EDF1-4 and ERF1, and in JA signaling, including MYC2 and WRKY33. JA signaling repression also resulted in indehiscent anthers via the downregulation of MYB26, NST1, NST2, and MYB85. These results not only provide new insight into the functions of ACS and ETR1 orthologs but also uncover their functional interactions with other hormone signaling pathways, such as GA–DELLA and JA, in plants.